Tax Avoidance Assessment In Relation To The Institutional Ownership, Size Of The Company, And Profitability - Rizqi, Reza Muhammad; Pratiwi, Aliah (Jurnal Riset Akuntansi Terpadu, 2024)
Utilizing legal loopholes in a country's tax code, tax avoidance is a strategy that aims to lower the amount of taxes that a nation imposes. Tax avoidance is a technique that is carried out by taxpayers, including individuals and corporations, with the intention of lowering the amount of tax that is required to be paid without breaching any current or applicable tax legislation. The objective of this study is to investigate the relationship between tax avoidance and factors such as profitability, company size, and institutional ownership. Manufacturing companies that are part of the consumer products industrial sector and are listed on the Indonesia Stock Exchange throughout the period of 2019–2023 are the focus of this research. Researchers carried out a variety of statistical analyses, including descriptive statistical tests, tests of coefficient similarity (pooling), tests of classical assumptions, multiple linear analysis, and hypothesis testing. In light of the findings, it was determined that factors such as profitability, company size, and institutional ownership all have a role in tax avoidance.